2017
DOI: 10.2174/1874325001711010687
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in the Treatment of Ankle and Subtalar Instability

Abstract: It was nearly a centenary ago that severe ankle sprain was recognized as an injury of the ankle ligament(s). With the recent technological advances and tools in imaging and surgical procedures, the management of ankle sprains - including subtalar injuries - has drastically improved. The repair or reconstruction of ankle ligaments is getting more anatomical and less invasive than previously. More specifically, ligamentous reconstruction with tendon graft has been the gold standard in the management of severely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…About one‐third of these individuals suffer significant disability due to pain, functional instability, mechanical instability, or recurrent sprains after recovery 4,6,9 . To date, no registered therapeutics exist that enables regeneration of injured ligaments 10 …”
Section: Introductionmentioning
confidence: 99%
“…About one‐third of these individuals suffer significant disability due to pain, functional instability, mechanical instability, or recurrent sprains after recovery 4,6,9 . To date, no registered therapeutics exist that enables regeneration of injured ligaments 10 …”
Section: Introductionmentioning
confidence: 99%
“…High-resolution MRI of the ankle and subtalar joint facilitates the identification and differentiation of the ligament injury prior to surgical reconstruction. Intraoperative stress fluoroscopy and subtalar arthroscopy can be performed to visualize subtalar joint laxity and synovitis and diagnose associated ligamentous lesions [ 4 , 25 ]. Recent MRI studies have indicated that IOLV in tarsal sinus and CFL are important stabilizers of the subtalar joint [ 3 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic ankle instability resulting in reduced level of physical function or decreased quality of life is a significant health problem for patients [ 2 ] . Besides, it could cause a significantly increased risk of post-traumatic arthritis in the ankle joint [ 1 , 3 5 ]. Standard operative procedures for chronically unstable ankles included anatomical repair, non-anatomic, and anatomic reconstruction [ 6 ].…”
Section: Introductionmentioning
confidence: 99%